Nye vekstmuligheter for fiskeoppdrett i Nord Norge - Trondsen, Torbjørn; Jørgensen, Øyvind (Nordlys, 2016)
Printer-friendly version of the Publisher's Version, published in the paper issue of Nordlys and online in Nordlys Nordnorsk debatt .